Lucy Lethbridge: Servants: A Downstairs View of Twentieth-century Britain - Clark, Letitia (Petits Propos Culinaires, 2013)
Lucy Lethbridge: Servants: A Downstairs View of Twentieth-century Britain: Bloomsbury Publishing Plc, 2013, 385 pp., hardback, £20.00.